The genetic landscape of axonal neuropathies in the middle-aged and elderly: Focus on MME. (15th December 2020) - Senderek, Jan; Lassuthova, Petra; Kabzińska, Dagmara; Abreu, Lisa; Baets, Jonathan; Beetz, Christian; Braathen, Geir J.; Brenner, David; Dalton, Joline; Dankwa, Lois; Deconinck, Tine; De Jonghe, Peter; et al.
Abstract : Objective: To test the hypothesis that monogenic neuropathies such as Charcot-Marie-Tooth disease (CMT) contribute to frequent but often unexplained neuropathies in the elderly, we performed genetic analysis of 230 patients with unexplained axonal neuropathies and disease onset ≥35 years. Methods: We recruited patients, collected clinical data, and conducted whole-exome sequencing (WES; n = 126) and MME single-gene sequencing (n = 104). We further queried WES repositories for MME variants and measured blood levels of the MME -encoded protein neprilysin. Results: In the WES cohort, the overall detection rate for assumed disease-causing variants in genes for CMT or other conditions associated with neuropathies was 18.3% (familial cases 26.4%, apparently sporadic cases 12.3%). MME was most frequently involved and accounted for 34.8% of genetically solved cases. The relevance of MME for late-onset neuropathies was further supported by detection of a comparable proportion of cases in an independent patient sample, preponderance of MME variants among patients compared to population frequencies, retrieval of additional late-onset neuropathy patients with MME variants from WES repositories, and low neprilysin levels in patients' blood samples. Transmission of MME variants was often consistent with an incompletely penetrant autosomal-dominant trait and less frequently with autosomal-recessive inheritance. Conclusions: A detectable fraction of unexplained late-onset axonal neuropathies is genetically determined, by variants in either CMT genes or genes involved in other conditions that affect the peripheral nerves and can mimic a CMT phenotype. MME variants can act as completely penetrant recessive alleles but also confer dominantly inherited susceptibility to axonal neuropathies in an aging population.